Extracellular Vesicles Work as a Functional Inflammatory Mediator Between Vascular Endothelial Cells and Immune Cells - Hosseinkhani, Baharak; Kuypers, Sören; van den Akker, Nynke M. S.; Molin, Daniel G. M.; Michiels, Luc (Frontiers in Immunology, 2018)
Extracellular vesicles (EV) mediated intercellular communication between monocytes and endothelial cells might play a major role in vascular inflammation and atherosclerotic plaque formation during cardiovascular diseases. Whilst critical involvement of small (exosomes) and large EV (microvesicles) in cardiovascular diseases has recently been appreciated, the pro- and/or anti-inflammatory impact of a bulk EV (exosomes+ microvesicles) on vascular cell function as well as their inflammatory capacity are poorly defined. This study aims to unravel the immunomodulatory content of EV bulk-derived from control (uEV) and TNF-α induced inflamed endothelial cells (tEV) and to define their capacity to affect the inflammatory status of recipients monocytes (THP-1) and endothelial cells (HUVEC) in vitro. Here, we show that EV derived from inflamed vascular endothelial cells were readily taken up by THP-1 and HUVEC. Human inflammation antibody array together with ELISA revealed that tEV contain a pro-inflammatory profile with chemotactic mediators, including ICAM-1, CCL-2, IL-6, IL-8, CXCL-10, CCL-5 and TNF-α as compared to uEV. In addition, EV may mediate a selective transfer of functional inflammatory mediators to their target cells and modulate them towards either pro-inflammatory (HUVEC) or anti/pro-inflammatory (THP-1) mode. Accordingly, the expression of pro-inflammatory markers (IL-6, IL-8 and ICAM-1) in tEV treated- HUVEC was increased. In the case of THP-1, EC-EV do induce a mixed of pro and anti-inflammatory response as indicated by the elevated expression of ICAM-1, CCL-4, CCL-5 and CXCL-10 proteins. At the functional level, EC-EV mediated inflammation and promoted the adhesion and migration of THP-1. Taken together, our findings proved that the EV released from inflamed endothelial cells were enriched with a cocktail of inflammatory markers, chemokines and cytokines which are able to establish a targeted cross-talk between endothelial cells and monocytes and reprogramming them towards a pro or anti-inflammatory phenotypes.